Regreening Africa Dashboard - CGIAR Research Program on Water, Land and Ecosystems (2021)
The Regreening Africa Dashboard is an interactive land restoration decision dashboard, being developed as part of the EU-funded Regreening Africa Project. WLE provided resources as part of the co-design of the Rwanda country dashboard in particular.